Respuesta :

Answer:

6

Step-by-step explanation:

They got 3x-12 because they took

3(x - 4)

and they distrubuted the 3 to the numbers in parenthesis,

how they did this was they multiplied 3 by x and got 3x then they kept the subtraction sign that is in the parenthesis. Then they multiplied 3 by the 4 and got 12.

then the equation was 3x - 12/2 = 6

obed45

Answer:

x=8

Step-by-step explanation:

[tex] \frac{3(x - 4)}{2} = 6[/tex]

Multiply 3 by what's in the bracket

[tex] \frac{3x - 12}{2} = 6[/tex]

Multiply through by the LCM of all the denominators

[tex] \frac{2(3x - 12)}{2} = 2 \times 6[/tex]

=The numerator 2 will cancel the denominator 2

[tex]3x - 12 = 12[/tex]

Grouping like terms

[tex]3x = 12 + 12[/tex]

Dividing both sides by 3

[tex] \frac{3x}{3 } = \frac{24}{3} [/tex]

[tex]x = 8[/tex]

ACCESS MORE